Arbitration settlement of disputes concerning administrative contracts in Romania - Cătălin-Silviu Săraru (Juridical Tribune, 2018)
The present study aims to analyze the conditions under which arbitration may be used in the administrative contracts provided by the Civil Code and the legislation on public procurement and concessions. In the administrative law doctrine, the provision on the possibility to resort to arbitration in litigation regarding the administrative contracts is often expressed, because the competent administrative court and, on the other hand, the arbitration is a specific institution of commercial law, where the parties are in a position of legal equality. In our opinion, in relation to the positive law provisions previously analyzed, we consider that it is no longer possible to deny the possibility of inserting, under the law, the arbitrary arbitration clauses in litigations concerning administrative contracts.